An All-Fiber Supercontinuum Source With 30.6-W High-Power and Ultrawide Spectrum Ranging From 385 nm to Beyond 2400 nm - Xin Zou; Jifang Qiu; Xiaodong Wang; Zi Ye; Chang Sun; Tingwu Ge; Jian Wu (IEEE Photonics Journal)
An all-fiber high power, blue-enhanced supercontinuum generation in a piece of uniform photonic crystal fiber pumped by a picosecond Yb-doped master oscillator power amplifier (MOPA) is experimentally demonstrated. The MOPA source is seeded by an actively dissipative soliton mode-locked Yb-doped fiber laser with a fundamental repetition rate of approximately 15.33 MHz and a large chirp. By introducing giant chirp to the seed pulses and optimizing the pump power in every stage of the MOPA, an SC with 30.6-W output average power and an extremely wide spectrum of 385 nm to beyond 2400 nm is obtained.